Sonification of Arm Movements in Stroke Rehabilitation – A Novel Approach in Neurologic Music Therapy - Scholz, Daniel S.; Rohde, Sönke; Nikmaram, Nikou; Brückner, Hans-Peter; Großbach, Michael; Rollnik, Jens D.; Altenmüller, Eckart O. (Frontiers in Neurology, 2016)
Gross-motor impairments are common after stroke, but efficient and motivating therapies for these impairments are scarce. We present an innovative musical sonification therapy especially designed to retrain patients' gross-motor functions. Sonification should motivate patients and provides additional sensory input informing about relative limb position. Twenty-five stroke patients were included in a clinical pre-post study and took part in the sonification training. The patients' upper extremity functions, their psychological states and their arm movement smoothness were assessed pre and post training. Patients were randomly assigned to either of two groups. Both groups received an average of ten days (M = 9.88; SD = 2.03; 30min/day) of musical sonification therapy (music group, MG) or a sham sonification movement training (control group, CG), respectively. The only difference between the two protocols was that in the CG no sound was played back during training. In the beginning, patients explored the acoustic effects of their arm movements in space. At the end of the training, the patients played simple melodies by coordinated arm movements. The 15 patients in the MG showed significantly reduced joint pain (F = 19.96, p < 0.001) in the Fugl-Meyer Assessment after training. They also reported a trend to have improved hand function in the Stroke Impact Scale as compared to the control group. Movement smoothness at day one, day five and the last day of the intervention was compared in MG patients and found to be significantly better after the therapy. Taken together, musical sonification may be a promising therapy for motor impairments after stroke but further research is required since estimated effect sizes point to moderate treatment outcomes.